OPTIMALISASI PELAPORAN KEUANGAN MELALUI APLIKASI SIMPATI PADA LAZNAS YATIM MANDIRI PURWOKERTO - Maryani, Ina; Dwi Mulyanto, Joko; Fedel, Perdana Putra; Utari, Yesita Adityas (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Laznas Yatim Mandiri Purwokerto is currently facing several problems because it does not yet have an effective financial recording and reporting system or application. The problems faced by Yatim Mandiri Purwokerto include lack of accuracy in financial recording. Another problem is the difficulty in making decisions because the data is not real-time, the lack of integrated information, namely financial information is scattered and not integrated, making it difficult for comprehensive analysis. Seeing these various problems, the solution offered is to implement the SIMPATI application with the aim that it can be an effective solution in overcoming the problems faced by Yatim Mandiri Purwokerto. Through the SIMPATI application can improve the accuracy and efficiency of financial recording, speed up the financial reporting process, increase transparency and accountability, provide real-time data for better decision making and can increase donor confidence through transparent reporting. Thus the SIMPATI application can bring significant changes in the financial management of Lasnas Yatim Mandiri Purwokerto, improving overall organizational performance. The outputs in this community service activity include: producing an integrated SIMPATI application that can be developed and implemented at Laznas Yatim Mandiri Purwokerto, the application is equipped with features that support the financial management of Laznas Yatim Mandiri Purwokerto. Keywords: Application; SIMPATI; Financial Management